African greenfield investment and the likely effect of the African Continental Free Trade Area - Anirudh Shingal; Maximiliano Mendez Parra (Indian Council for Research on International Economic Relations (ICRIER), 2020)
Using sector-level data on bilateral greenfield investment for 198 source and destination countries over 2003-2018 in a structural gravity model, we examine the likely effect of the African Continental Free Trade Area (AfCFTA) on African investment. Conditional general equilibrium estimates from counterfactual analysis show that the stock of intra-African greenfield investment in 2018 would have increased by 14 percent from a successful implementation of the AfCFTA in that year relative to the baseline scenario of no agreement. Exploring possible transmission channels for the investment- enhancing effect of the AfCFTA, we find the intra-African trade elasticity of greenfield investment to be positive, including for intermediates, especially in host countries with strong governance indicators. However, the effect of regulatory cooperation via bilateral investment treaties is found to be negative. This suggests that trade liberalization under the AfCFTA is more likely to foster intra-African investment via its positive effect on intra-African trade.
Keywords: E22; F21; 330; Africa; greenfield investment; fDI Markets; AfCFTA; gravity model; conditional GE; counterfactual analysis; transmission channels